Hydrological controls on glacially exported microbial assemblages. Issue 5 (6th May 2017) - Dubnick, Ashley; Kazemi, Sina; Sharp, Martin; Wadham, Jemma; Hawkings, Jon; Beaton, Alexander; Lanoil, Brian
Abstract: The Greenland Ice Sheet (GrIS) exports approximately 400 km 3 of freshwater annually to downstream freshwater and marine ecosystems. These meltwaters originate in a wide range of well‐defined habitats that can be associated with very different physical environments within the ice sheet, ranging from oxygenated surface environments that are exposed to light and supplied with nutrients from atmospheric/aeolian sources to subglacial environments that are permanently dark, isolated from the atmosphere, and potentially anoxic. Hydrological conditions in the latter likely favor prolonged rock‐water contact. The seasonally evolving hydrological system that drains meltwaters from the GrIS connects these distinct microbial habitats and exports the microbes contained within them to downstream ecosystems. The microbial assemblages exported in glacier meltwater may have an impact on downstream ecosystem function and development. We explored how the seasonal development of a glacial drainage system influences the character of microbial assemblages exported from the GrIS by monitoring the seasonal changes in hydrology, water chemistry, and microbial assemblage composition of meltwaters draining from a glacier in southwest Greenland. We found that the microbial assemblages exported in meltwaters varied in response to glacier hydrological flow path characteristics. Whether or not meltwaters passed through the subglacial environment was the first‐order control on the composition of the microbial assemblages exported from the glacier, while water source (i.e., supraglacial or extraglacial) and subglacial residence times were second‐order controls. Glacier hydrology therefore plays a fundamental role in determining the microbial exports from glaciated watersheds. Plain Language Summary: Glacier meltwater volume is increasing as the result of a warming climate. Much of this water is transported beneath the glacier. We examined the impact of passing through the subglacial environment on the microorganisms in the water: these microorganisms are the only living things in this environment and have the potential to strongly influence downstream marine ecosystems. We found that passing through the subglacial environment changed the microbial communities and that the amount of time spent and the source of the water were secondary, but still important, influences on the microbial communities leaving the glacier. These findings, combined with previous observations that subglacial environments around the world host similar microbial communities, indicate that meltwater that passes beneath glaciers may house similar microbial communities and that these communities have the potential to affect downstream ecosystems. Key Points: The subglacial environment provides a first‐order control on the microbial assemblages exported in glacial meltwater Water source (i.e., supraglacial or extraglacial) and subglacial residence time are second‐order controls on the microbial assemblages exported in glacial meltwater